(untitled) (Archives of Mechanics - Test, 2000)
The self-similar problem of stress singularity at the notch in infinite two-dimensional elastic orthotropic body was considered. The considerations were restricted to the notches symmetrically oriented with respect to the axes of orthotropy. Both, the extension and shear modes were studied. It was confirmed that in the limiting case of zero opening angle (semi-infinite crack), the order of singularity is the same as in the case of isotropic material -r-1/2. This is not true in the case of finite opening angles. If the orientation of the notch axis is parallel to the axis of maximal stiffness, the order of singularity is lower than that for the case of perpendicular orientation. In the last case, if the ratio ET/EL is small enough, then the order of singularity in tension does not practically decrease with growing opening angle 2α up to α â‰‚ π/4.